PERCEPTIONS OF COUNSELING AND MEDITATIONS IN DIVORCE EXPERIENCE: FROM LAWYERS, COUNSELORS AND LEGAL AID CLIENTS (PERAK, MALAYSIA) - S. Annie Margaret; Zawawi Abu Bakar; Siti Rozaina Binti Kamsani (Jurnal Penyelidikan Sains Sosial, 2021)
Divorce is one of the most challenging parts of anyone’s life once divorce occurs,the couples will have to make themselves ready to go to the divorce proceedings. In fact, formany couples, even contacting a matrimonial lawyer and seeking counselling is a set of newexperiences.Unfortunately, the poor service during the reconciliation process, together withinherently destructive problems, made their marriage irretrievably broken down, and the onlyavailable option left was to divorce At this point together with their emotional rollercoasterthey attend mediation The purpose of this paper is to describe included in-depth interviews theresults of a study of 14 clients of the Legal Aid Department spouses who were divorced between2017 till 2018 and were the individuals who open a divorce on the ground that the marriagehas irretrievably broken down under section 54 of the Law Reform Marriage Act, 1976. Thepresent research outlines that even though the law designed a provisions to encouragereconciliation yet experiences over the counseling divorce process have also been align withother well-known researchers like Mimi Kamariah, Nora Abdul Hak, Noraini Hashim, NurEzan Rahmat, Najibah Md. Zain, and Sarafuddin Abdul Syahid Sowell . Poor service duringthe reconciliation process, together with inherently destructive problems, made their marriageirretrievably broken down, and the only available option left was to divorce. Even though thiswas not the best option, this seems the only option to end this wretchedly unhappy marriage